2018
DOI: 10.1186/s12882-018-1174-0
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of uremic encephalopathy and bilateral basal ganglia lesions in non-diabetic hemodialysis patient: a case report

Abstract: BackgroundUremic encephalopathy (UE), a toxic metabolic encephalopathy, is an uncommon complication resulting from endogenous uremic toxins in patients with severe renal failure. UE syndrome can range from mild inattention to coma. The imaging findings of UE include cortical or subcortical involvement, basal ganglia involvement and white matter involvement. The basal ganglia type is uncommon, although previous cases have reported that Asian patients with diabetes mellitus (DM) are usually affected.Case present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
(41 reference statements)
0
3
0
Order By: Relevance
“… 24 However, in a case study in 2018 Liu reported a non-diabetic UE with typical bilateral basal ganglia lesions. 25 In our study, none of the 20 patients showed symptoms of basal ganglia involvement on their MRI images. Since the presence of DM was considered as an exclusion criterion in our study, the DM can be suggested as an exacerbating, not a definite, factor for basal ganglia involvement.…”
Section: Discussionmentioning
confidence: 46%
“… 24 However, in a case study in 2018 Liu reported a non-diabetic UE with typical bilateral basal ganglia lesions. 25 In our study, none of the 20 patients showed symptoms of basal ganglia involvement on their MRI images. Since the presence of DM was considered as an exclusion criterion in our study, the DM can be suggested as an exacerbating, not a definite, factor for basal ganglia involvement.…”
Section: Discussionmentioning
confidence: 46%
“…The patient's deteriorating renal function, as indicated by elevated serum creatinine and blood urea nitrogen (BUN) levels, provided a crucial clue for considering uremic encephalopathy in the differential diagnosis. Chronic alcoholism can lead to renal impairment through multiple mechanisms, such as direct toxic effects of alcohol on the kidneys and dehydration secondary to alcohol consumption [5].…”
Section: Discussionmentioning
confidence: 99%
“…As there are currently no clinical methods that can quantify cerebral urea levels in vivo , the literature surrounding uremic encephalopathy has mainly focused on evidence derived from plasma creatinine and blood-urea nitrogen levels. Case reports of patients with uremic encephalopathy caused by renal failure showed an estimated 1.82–3.59 FC decrease in blood-urea nitrogen levels following dialysis and remission of symptoms related to uremic encephalopathy ( Kim et al, 2016 ; Jia et al, 2017 ; Gong et al, 2018 ). Although these reports reflect systemic urea levels, and, thus, cannot be directly compared with corresponding measurements from the cerebral tissues, the case-control FC observed in the present study of VaD approximates those present in cases of uremic encephalopathy.…”
Section: Discussionmentioning
confidence: 99%